2006
DOI: 10.1080/00498250600815906
|View full text |Cite
|
Sign up to set email alerts
|

Disposition of 2,2′,4,4′,5,5′-hexabromodiphenyl ether (BDE153) and its interaction with other polybrominated diphenyl ethers (PBDEs) in rodents

Abstract: 1.The disposition of the 14 C-labeled polybrominated diphenyl ether (PBDE), 2,2′,4,4′,5,5′-hexaBDE (BDE153) was investigated in rodents following single and multiple doses and in a mixture with radiolabeled 2,2′,4,4′-tetraBDE (BDE47) and 2,2′,4,4′,5-pentaBDE (BDE99). 2.In single exposure studies, there was little or no effect of dose on BDE153 disposition in male rats in the range of 1-100 µmol/kg. No major sex or species differences in the in vivo fate of BDE153 were detected. BDE153 was: 1) approximately 70%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 21 publications
7
66
0
Order By: Relevance
“…Additional studies performed in rodents with 14 C-BDE-47 confirmed that the majority of residues were contained in adipose tissue (Darnerud and Risberg, 2006;Sanders et al, 2006). Sanders et al (2006) examined the impact of repeat dosing on the disposition of BDE-47 in male rats. Doses of 0.1 μmol/kg (approximately 0.05 mg/kg) of 14 C-BDE-47 were administered for 1, 5, or 10 consecutive days.…”
Section: Bde-47mentioning
confidence: 99%
See 2 more Smart Citations
“…Additional studies performed in rodents with 14 C-BDE-47 confirmed that the majority of residues were contained in adipose tissue (Darnerud and Risberg, 2006;Sanders et al, 2006). Sanders et al (2006) examined the impact of repeat dosing on the disposition of BDE-47 in male rats. Doses of 0.1 μmol/kg (approximately 0.05 mg/kg) of 14 C-BDE-47 were administered for 1, 5, or 10 consecutive days.…”
Section: Bde-47mentioning
confidence: 99%
“…They were 2'-hydroxy-2,4,4'-triBDE, 3'-hydroxy-2,4,4'-triBDE, 4'-hydroxy-2,2',4-triBDE, 6-hydroxy-2,2',4,4'-tetraBDE, 2'-hydroxy-2,3',4,4'-tetraBDE, 3-hydroxy-2,2',4,4'-tetraBDE, 5-hydroxy-2,2',4,4'-tetraBDE, 4'-hydroxy-2,2',4,5'-tetraBDE and 4-hydroxy-2,2',3,4'-tetraBDE. Analysis of biliary metabolites collected from rats receiving 1 μmol/kg (ca 0.5 mg/kg) 14 C-BDE-47 intravenously (Sanders et al, 2006), resulted in the identification of two glutathione conjugates, namely 5-(glutathion-S-yl)-2,2',4,4'-tetraBDE and 6-(glutathion-S-yl)-2,2',4,4'-tetraBDE. In the metabolic pathway proposed by the authors the glutathione conjugates were formed through an arene oxide intermediate.…”
Section: Bde-47mentioning
confidence: 99%
See 1 more Smart Citation
“…Orn and Klasson-Wehler (1998) found that BDE 47 was persistent in the rat, but rapidly excreted in urine in mice. In a recent study, Sanders et al (2006) found that BDE 99 was the most rapidly metabolized congener of BDEs 47, 99, and 153 following single and multiple doses of radiolabelled mixtures of these three congeners administered by gavage to rodents (rats and mice). This contradicts the extrapolation by Geyer et al (2004) which resulted in a more rapid half-life for BDE 47.…”
mentioning
confidence: 99%
“…Studies in rodents have likewise measured absorption of BDE-47, -99, -100, -153, and -154 in the range of ~70-90%. [53][54][55] However, other studies that have exposed fish to unlabeled PBDEs through the diet have measured lower assimilation efficiencies of some congeners, including BDE-99, BDE-153, BDE-183, and BDE-209 suggesting species-specific differences in assimilation efficiencies of PBDEs possibly due to differences in metabolic enzyme systems. [56][57][58] For instance, BDE-209 absorption in some teleost fishes has been shown to occur at a slow rate, which may allow for greater metabolism and elimination than seen in terrestrial species.…”
Section: Pbde Uptake and Tissue Distributionmentioning
confidence: 88%